Sustainable Human Development: Corporate challenges and potentials. The case of Bayer CropScience's cotton seed production in rural Karnataka (India) - Jürgen Volkert; Harald Strotmann; Regina Moczadlo (Helmholtz-Zentrum für Umweltforschung (UFZ), 2014)
This paper aims to explore concepts, methods and empirical results of potential impacts of Transnational Corporations (TNC) on Sustainable Human Development (SHD) in emerging market countries. In doing so, a further major goal is to explain, illustrate and discuss how the theoretical CA framework used in the GeNECA project2 can be applied to corporate SHD impacts. Our findings are based on the case of Bayer CropScience's Model Village Project in rural Karnataka, India. To achieve our goals, we first establish a theoretical framework for assessing corporate impacts on SHD to capture SHD effects. Thereafter, we introduce the case of Bayer CropScience's seed production in rural India, for which a Model Village Project (MVP) has been established to explore ways, potentials and challenges of promoting SHD of the villagers and corporate goals in a win-win-strategy. Afterwards, we explain methodological requirements, our representative database for the quantitative analyses, and the qualitative methods that we use for project evaluation. Based on findings of the authors' external evaluation of the MVP, we discuss the baseline situation in the model villages with respect to corporate potentials, challenges and limitations to foster SHD impacts. Methodologically, we find the combination of quantitative representative methods and qualitative assessments to be most effective to capture corporate potentials and risks. Furthermore it turns out to be promising to extend the analyses beyond standardized benchmarks like the MDGs. We show that major determinants of SHD established in the paper result in a portfolio of corporate opportunities and risks. For instance, the reality of underemployment in the model villages provides specific corporate opportunities like an abundant pool of labor supply. However, it also produces corporate risks, e.g. lack of capital available for necessary investment by suppliers who frequently suffer from poverty, risk of over-indebtedness and a resulting inability to accumulate enough capital and to raise productivity. In the comprehensive opportunity and riskportfolio of this Bayer CropScience case, we find abundant potential business cases which we discuss further in the text. We conclude that corporate potentials as well as risks of corporate neglect and violations of people-centered SHD also depend on how much the villagers are enabled and empowered to make most of their agency as individuals and as groups. Furthermore, it depends on trust building as a prerequisite of awareness raising of the villagers themselves, so that they are willing and able to participate successfully in the undertaken procedures.
Keywords: 330